THE IMPACT OF THE JOINT BUSINESS GROUP (KUBE) PROGRAM ON THE SOCIO-ECONOMIC LIFE OF POOR FISHERMEN IN NAGARI TARATAK, SUTERA DISTRICT, PESISIR SELATAN REGENCY - Yanti Sri Wahyuni; Harisnawati Sri Harisnawati; Sri Rahayu; Lisa Nurariyanti; Dewi Wulandari (LPPM Universitas PGRI Sumatera Barat, 2024)
Poverty has always been closely associated with farming and fishing communities, due to their inability to meet daily basic needs for survival and their lack of income. Compared to farmers, the poorest group in Sutera District is the fishermen, numbering 2,140 individuals (Padang Ekspres, April 21, 2012). Most residents of Pesisir Selatan depend on food crop agriculture, fisheries, and trade, while other potential resources include plantations and tourism. The majority of residents live along the coastline stretching from north to south. Their primary livelihoods are farming and fishing. Administratively, Pesisir Selatan Regency consists of 12 districts, 76 nagari (villages), and 364 kampung (hamlets). One of the poorer districts is Sutera, which consists of four nagari: Surantih, Taratak, Ampiang Parak, and Amping Parak Timur, with a population of 49,019. This study aims to describe the impact of empowerment programs on the socio-economic life of poor fishing households in Nagari Taratak, Sutera District, Pesisir Selatan Regency. The research method used is qualitative, with data collected through observation and in-depth interviews with informants selected using snowball sampling. Data validity was tested using triangulation, and analysis was carried out using the interactive model developed by Mathew Miles and Huberman. The program’s social impact included closer social interactions after the establishment of KUBE, stronger cooperation, and reduced competition. Its economic impacts can be seen in new employment opportunities for fishermen’s wives and children, increased income, and improved educational attainment among fishermen’s children. The KUBE program has therefore contributed positively to the economic life of fishermen who made use of it.